Rising trend in pediatric eosinophilic esophagitis incidence in Spain: Results of a prospective study 2014¿16 - La Orden Izquierdo, Enrique; Mahillo Fernández, Ignacio; Fernández Fernández, Sonia; Barrio Torres, Josefa; Román Riechmann, Enriqueta; Gutiérrez Junquera, Carolina (My University, 2021)
Objectives: The rate of eosinophilic esophagitis (EoE) diagnosis is increasing. This study aims to determine the incidence of EoE in the pediatric population residing in the southwestern Madrid and to analyze whether absolute monthly pollen counts, modified or not by the principal atmospheric pollutants, are associated with it. Methods: A cross-sectional study on prospectively recruited patients was designed to calculate the incidence of EoE in children aged under 15 years who were diagnosed between September 2014 and August 2016 in twelve hospitals. We collected demographic and symptoms data, date of onset of symptoms, date of medical consultation, and date of endoscopic diagnosis of each included patient. Relative risk estimation was performed to assess the association between the incidence of diagnosis and monthly pollen counts and levels of atmospheric pollutants. All these models were adjusted for the number of total patients that underwent endoscopy at first time. Results: One hundred forty-eight patients were included. The most frequent symptoms were abdominal pain [42.57%], dysphagia [42.57%], and impaction [39%¿ 86%]. The median overall monthly incidence was 1.13 [interquartile rank: 0.97¿1.43] cases/100,000 children, and the annual mean was 15.2. The overall analysis of the relationship between incidence and absolute monthly counts, corrected for the number of first-time endoscopies performed, revealed no statistically significant association with pollen and air pollutants. There was a higher frequency of diagnosis during the pollination period of Cupressaceae [relative risk 1.647; 95% CI (1.192¿2.276) p < .002] and during February and November (relative risk 1.67; p < .01). Conclusions: This study confirms the high incidence of eosinophilic esophagitis and also suggests a period of higher incidence of diagnosis in the months of February and November as well as in the period of high pollination of Cupressaceae.